The Business of Climate Change: A Perspective of Environmental Performance on the Tourism Industry. - Ms. M. van der Bank (African Journal of Hospitality, Tourism and Leisure, 2018)
Climate change has increasingly attracted tourist attention in the past decade, because tourism is likely to be affected both by climate change itself and by policies implemented to address it. Corporate reaction could be viewed in three ways to climate change regulations, namely supportive, neutral or defensive. The perspective examines the critical relationship between the tourism sector and sustainable development, examining global trends and the problems they raise, exploring the current set of solutions being implemented, and offering some new ideas for better managing the relationship. The Climate and Sustainable Tourism Model that is a suitable framework encapsulates many of the issues explored and offer insights for policy makers seeking to develop better solutions to vexing climate change issues. Sustainable development is particularly important in the South African context if one considers, for example the fact that Africa has economic uncertainty, intractable conflict, rising prices for food and oil and the effects of climate change on agricultural land and tourism which are all problems that need to be addressed. The government must be the central co- coordinator and leader, because the government holds many tools, which are essential to coordinate and develop and enforce new rules. The main purpose of the regulations is to set up climate change policies, strategies, plans and measures as well as to cooperate with the private sector and with the international actors.